2(4h-6)=4(3b-7)

Simple and best practice solution for 2(4h-6)=4(3b-7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(4h-6)=4(3b-7) equation:


Simplifying
2(4h + -6) = 4(3b + -7)

Reorder the terms:
2(-6 + 4h) = 4(3b + -7)
(-6 * 2 + 4h * 2) = 4(3b + -7)
(-12 + 8h) = 4(3b + -7)

Reorder the terms:
-12 + 8h = 4(-7 + 3b)
-12 + 8h = (-7 * 4 + 3b * 4)
-12 + 8h = (-28 + 12b)

Solving
-12 + 8h = -28 + 12b

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + 12 + 8h = -28 + 12 + 12b

Combine like terms: -12 + 12 = 0
0 + 8h = -28 + 12 + 12b
8h = -28 + 12 + 12b

Combine like terms: -28 + 12 = -16
8h = -16 + 12b

Divide each side by '8'.
h = -2 + 1.5b

Simplifying
h = -2 + 1.5b

See similar equations:

| x-3/2-4x-1/6=2/3 | | 2x^3/16x^15 | | (10^(-15))/(3.9*10^7)= | | 4y+5y+15=5y+7y | | 79-13x+13x=49-14x+x^2+13x | | -19m+14b= | | 3/4x-6=1/12x | | 6x/2-x/1=x/10-28/5 | | 15-30=6x-(x+5) | | -5(2x+1)+19=-2(x+5) | | 0.2(x+40)-0.02(x-50)=19.8 | | 30=s(x+1) | | 181=-(1-13m) | | y=5/7x-20 | | 8f-2f=-16 | | 19x+26=x+8 | | -0.2x^2+0.8x+1=0 | | 15z-13z= | | 15t+38=10t+13 | | N-7+6=12 | | 14x+14=12x | | 1/4a-2/3a=5/6 | | 2(3y+5)=3(5y+13) | | -6(2p-5q)= | | 2x^2-45x-91=0 | | 4X-1/3=11 | | X/12=5/32 | | 10p-p=2p | | 5x12=5/32 | | 4x-12=49 | | 13(p+q)= | | 13-(3/2x)=37 |

Equations solver categories